2015
DOI: 10.1037/apl0000013
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of diversity training and diversity beliefs on team creativity in nationality diverse teams.

Abstract: Attaining value from nationality diversity requires active diversity management, which organizations often employ in the form of diversity training programs. Interestingly, however, the previously reported effects of diversity training are often weak and, sometimes, even negative. This situation calls for research on the conditions under which diversity training helps or harms teams. We propose that diversity training can increase team creativity, but only for teams with less positive pretraining diversity bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 97 publications
0
55
0
2
Order By: Relevance
“…This unexpected finding mirrors the results by Adair, Hideg and Spence (), who reported that cultural intelligence hinders the development of shared values in homogeneous teams. In a similar vein, Homan and colleagues () found that training team members’ competences in dealing with nationality diversity resulted in deteriorated team performance in teams that were nationally homogeneous, especially in teams that had a higher need for such a nationality diversity training programme. Possibly, diversity training or a culturally intelligent leader who endorses diversity induce a productivity‐oriented diversity belief that diverse groups have a performance advantage compared to homogeneous groups (Nakui, Paulus and Van der Zee, ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This unexpected finding mirrors the results by Adair, Hideg and Spence (), who reported that cultural intelligence hinders the development of shared values in homogeneous teams. In a similar vein, Homan and colleagues () found that training team members’ competences in dealing with nationality diversity resulted in deteriorated team performance in teams that were nationally homogeneous, especially in teams that had a higher need for such a nationality diversity training programme. Possibly, diversity training or a culturally intelligent leader who endorses diversity induce a productivity‐oriented diversity belief that diverse groups have a performance advantage compared to homogeneous groups (Nakui, Paulus and Van der Zee, ).…”
Section: Discussionmentioning
confidence: 94%
“…Even if diversity initiatives are implemented, their effectiveness varies considerably across empirical studies (Bezrukova, Jehn and Spell, ; Paluck, ). Thus, scholars have called for a better integration of the organizational context in order to understand the mechanics of successful nationality diversity management (Herdman and McMillan‐Capehart, ; Homan et al ., ). Given these critical evaluations of organizational practices, we adopt Rink and Ellemer's () idea that employees can recognize diversity as part of their organizational identity when they experience team diversity as a valuable asset for accomplishing team tasks (see also Ely and Thomas, ).…”
mentioning
confidence: 97%
“…Perhaps surprisingly, mere cultural or ethnic diversity of coworkers has been shown to correlate to creativity in fashion teams (Godart et al 2015) and the impact of scientific papers (Freeman and Huang 2014). Importantly, group diversity can work out different ways (Hülsheger et al 2009) and may only have clear positive effects if the people involved actually value such diversity (Homan et al 2015).…”
Section: Collect Diverse Experiencesmentioning
confidence: 99%
“…Research has provided evidence for the paradox related to inclusion of people from diverse background during periods of economic difficulties. On the other hand, there is evidence that workforce diversity can provide economic advantages such as creativity and innovation (e.g., Roberge and van Dick, 2010;Hoever et al, 2012;Homan et al, 2015), which can stimulate the economic engine needed to survive and thrive during periods of economic challenges. On the other hand, there is evidence that workforce diversity can provide economic advantages such as creativity and innovation (e.g., Roberge and van Dick, 2010;Hoever et al, 2012;Homan et al, 2015), which can stimulate the economic engine needed to survive and thrive during periods of economic challenges.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, research has indicated that during periods of economic hardship, individuals and nations are less hospitable and more exclusionary toward people who are different than the mainstream on various levels of diversity, such as gender, race and ethnicity, physical and mental abilities, LGBTQ, immigrant status, refugee status, and even nationality (e.g., Lesińska, 2014;Askanius and Mylonas, 2015;Tamamović, 2015;Van Vossole, 2016). On the other hand, there is evidence that workforce diversity can provide economic advantages such as creativity and innovation (e.g., Roberge and van Dick, 2010;Hoever et al, 2012;Homan et al, 2015), which can stimulate the economic engine needed to survive and thrive during periods of economic challenges.…”
Section: Introductionmentioning
confidence: 99%